Constructing Mg2Co–Mg2CoH5 nano hydrogen pumps from LiCoO2 nanosheets for boosting the hydrogen storage property of MgH2. Issue 42 (10th October 2022) - Zhang, Yan; Wu, Fuying; Guemou, Samuel; Yu, Haijie; Zhang, Liuting; Wang, Yijing
Abstract : Li + served as an "anchor" to facilitate the uniform distribution of a LiCoO2 "boat" among the MgH2 "ocean" and benefited the self-assembling of numerous Mg2 Co–Mg2 CoH5 "nano hydrogen pumps" on the surface of MgH2 during cycling. Abstract : Herein, an active positive electrode material, LiCoO2 nanosheets, was synthesized via a two-step method, which demonstrated a remarkable catalytic effect for the hydrogen storage property of MgH2 . Incorporated with LiCoO2 nanosheets, MgH2 started to release hydrogen at 180 °C and a desorption content as high as 5.5 wt% H2 was attained within 60 min at 250 °C. The dehydrogenation activation energy was significantly decreased to 48.5 ± 0.4 kJ mol −1, achieving a 68.9% reduction compared to MgH2 . It was verified by microstructural studies that Li + served as an "anchor" to facilitate a uniform distribution of LiCoO2 "boat" among the MgH2 "ocean", benefitting the self-assembly of numerous Mg2 Co–Mg2 CoH5 couples on the surface of MgH2 during the cycling process. Meanwhile, the in situ formed Mg2 Co–Mg2 CoH5 couples were not restricted to offering multiple channels for fast hydrogen diffusion but also worked as "nano hydrogen pumps" to accelerate Mg/MgH2 hydrogen charging and discharging. This study provides an interesting example of effective cooperation between Li + and Co 3+ on improving the catalytic action toward MgH2 . It shall shed light on efficient designing of high-efficient catalysts in hydrogen storage areas or other energy-related fields.